HVAD to HeartMate 3 left ventricular assist device exchange: Best practices recommendations. (24th March 2022) - Salerno, Christopher T; Hayward, Christopher; Hall, Shelley; Goldstein, Daniel; Saeed, Diyar; Schmitto, Jan; Kaczorowski, David; Molina, Ezequiel; Zimpfer, Daniel; Tsui, Steven; Soltesz, Edward; Pham, Duc Thin; et al.
Abstract: The HeartWare HVAD System (Medtronic) is a durable implantable left ventricular assist device that has been implanted in approximately 20, 000 patients worldwide for bridge to transplant and destination therapy indications. In December 2020, Medtronic issued an Urgent Medical Device Communication informing clinicians of a critical device malfunction in which the HVAD may experience a delay or failure to restart after elective or accidental discontinuation of pump operation. Moreover, evolving retrospective comparative effectiveness studies of patients supported with the HVAD demonstrated a signiﬁcantly higher risk of stroke and all-cause mortality when compared with a newer generation of a commercially available durable left ventricular assist device. Considering the totality of this new information on HVAD performance and the availability of an alternate commercially available device, Medtronic halted the sale and distribution of the HVAD System in June 2021. The decision to remove the HVAD from commercial distribution now requires the use of the HeartMate 3 left ventricular assist system (Abbott, Inc) if a patient previously implanted with an HVAD requires a pump exchange. The goal of this document is to review important differences in the design of the HVAD and HeartMate 3 that are relevant to the medical management of patients supported with these devices, and to assess the technical aspects of an HVAD-to-HeartMate 3 exchange. This document provides the best available evidence that supports best practices. (J Thorac Cardiovasc Surg 2022;-:1–8) Abstract : The HeartWare HVAD System (Medtronic) is a durable left ventricular assist device (LVAD) approved for bridge to transplant indication in 2012 and destination therapy indication in 2019, based on data from the ADVANCE + Continued Access Protocol, ENDURANCE, and ENDURANCE Supplemental clinical studies [1–5].